The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. I. Andasibe sahondrae, a new, peculiar genus and species of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) - Hlaváč, Peter; Baňař, Petr (Zootaxa, 2012)
Andasibe sahondrae, gen. nov. and sp. nov. is described based on one female collected by sifting in central Madagascar.The genus is a member of the supertribe Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae). It is placed into the subtribe Mastigerina, and this is a first record of the subtribe for Africa.